A Study of Shielding and Comfort Performance for Selected Fabrics Used as Casing Material for X-Ray Protective Aprons (Journal of Fiber Bioengineering and Informatics, 2018)
Lead aprons are typically worn by radiographers to protect them from harmful radiation. As such, agood radiation shield must have a high Lead Equivalence to minimize the transmitted radiation doseduring exposure. While most radiation shields fulfil this requirement by using matrices of lead andother substances, most aprons are uncomfortable to wear. Further, if the examination takes longer thanexpected, the radiographer will feel discomfort because of the heavy weight of the apron, or the smoothsurface of the coated casing material. Another issue is the poor fit and design of the aprons due tothe stiffness of the lead sheet. In general, the comfort characteristics of any textile material are relatedto air permeability, moisture management, abrasion resistance, fabric structure, thickness and weight,as well as yarn types. The objective of this study is to use standard testing methods to characterizesome selected fabrics in terms of their X-ray shielding ability, physical, mechanical, and morphologicproperties. The implication of this research will help for further study of this type of fabrics to improvethermal comfort of X-ray protective clothing.